Language Indices of Unity and Animosity - T. V. Leontyeva (Научный диалог, 2023)
The results of the implementation of the scientific project “The Semantics of Unity and Animosity in Russian Lexis and Phraseology: Language System and Discourse” supported by the Russian Science Foundation are presented. It is based on the thesis that language acts as a way of indexing referents — realities and ideas about reality. The semantic-motivational approach to the study of the vocabulary and phraseology of unity and enmity confirms that the ways of conceptualizing reality are characterized by regular reproducibility. The study of the semantics of words, especially in the context of changes in the lexical composition of the Russian, one way or another affects not only linguistic, but also worldview issues. The examples show that a linguistic unit “alone” can serve as a cultural sign if it is highly specific for a historical era. The study of arrays of new words is recognized as informative for solving the applied problem of monitoring sociocultural transformations. It is reported that the executors of the project have prepared “A Dictionary of Actual Vocabulary of Unity and Animosity in the Russian at the Beginning of the 21st Century” (2021) and “1000 Words of Unity and Animosity at the Beginning of the 21st Century: An Ideographic Dictionary” (2022).